2019
DOI: 10.1186/s12905-019-0816-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with pain of early medical abortion: qualitative results from Nepal, South Africa, and Vietnam

Abstract: Background Medical abortion (MA) has become an increasingly popular choice for women even where surgical abortion services are available. Pain is often cited by women as one of the worst aspects of the MA experience, yet we know little about women’s experience with pain management during the process, particularly in low resource settings. The aim of this study is to better understand women’s experiences of pain with MA and strategies for improving quality of care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Indeed, data regarding women's experience with pain in the postpartum period are limited. Grossman et al examined the pain experience of 42 women following early medical abortions 16 . Similar to our findings, many of the participants reported that counseling and education about pain management resulted in an improved experience with pain.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, data regarding women's experience with pain in the postpartum period are limited. Grossman et al examined the pain experience of 42 women following early medical abortions 16 . Similar to our findings, many of the participants reported that counseling and education about pain management resulted in an improved experience with pain.…”
Section: Discussionsupporting
confidence: 85%
“…Whereas recent research has emphasized the need for strengthened post-abortion family planning counselling, this analysis suggests that women's overall satisfaction with care is more related to whether their provider counsels them on the treatment procedure. That this association was significant after adjustment for women's rating of the comfort they felt during the procedure suggests that receiving counselling on treatment steps and the likely discomfort women will feel during the procedure helps women cope with pain and emotional stress (Grossman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found that clients' satisfaction with abortion-related care is associated with the interpersonal treatment by staff and the information provided, as well as the individual-level socio-demographic characteristics of clients (Graff & Tabbutt-Henry, 2003;Deitch et al, 2019). Studies have also shown that components and processes of care shape clients' satisfaction with care received, such as procedure type, facility type, intensity of pain felt during treatment and client choice of treatment method (Becker et al, 2011;Diaz-Olavarrieta, et al, 2012;Maternowska et al, 2015;Grossman, et al, 2019). Additional research has highlighted the relevance of other domains of quality of care to women's evaluation of quality, such as the accessibility of services, the facility environment, integration of family planning counselling and method provision and women's perception of provider's technical competence (Becker et al, 2011;Diaz-Olavarrieta, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have focused on populations of women in the United States, Canada, France, and Israel [3 , 5 , 12] . In a separate manuscript, we report on qualitative findings of study participants' experiences with the pain of medical abortion [13] .…”
Section: Discussionmentioning
confidence: 99%